Natural Food Toxins and its Ayurvedic Purview (International Journal of Ayurveda and Pharma Research, 2025)
Toxins are poison of plant or animal origin, produced by or derived from microorganisms and acting as an antigen in the body. These are formed in dietary articles as a part of the defence mechanism of the plant against predators or insects or in response to extreme climatic conditions. These secondary metabolites are chemical compounds having diverse structure and differ in biological function and toxicity, will have adverse impact on human or animal health when consumed in excess. Natural food toxins can be categorized under phytotoxins and marine toxins. Cyanogenic glycosides, glycoalkaloids, lectins, glucosinolates and pyrrolizidine alkaloids are the major phytotoxins. Marine or aquatic toxicity occurs by the ingestion of shellfish that have consumed toxin producing algae, or by bacterial growth in fish due to improper handling. Some of these toxins are extremely potent and harmful when consumed in large quantities. These toxins possess a serious health threat to both humans and livestock. It may result in acute and chronic toxicity ranging from gastrointestinal upset to fatality. So, detoxification of dietary articles containing natural food toxins is crucial as it helps to eliminate these chemicals and thereby ensuring food safety. So, this article intends to highlight the Ayurvedic viewpoint of natural food toxins and the importance of precautionary measures for preventing toxicity of natural food toxin from daily consuming dietary article.